Rancang Bangun Aplikasi Penentuan Solusi Perawatan Wajah berdasarkan Jenis Kulit Berbasis Website - Luluk Mufida; Naily Ikmalul Insiyah; Chika Labita; Arwin Datumaya Wahyudi Sumari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Skin is one of the essential and vital parts of the human body, especially the facial skin which is a mirror of beauty and health. However, sometimes people do not know the type of facial skin so they must consult a doctor. There are 5 types of facial skin, namely normal, oily, dry, sensitive and combination. Knowing the type of facial skin is very important to choose the right cosmetic product. In this research, the classification of facial skin types will be carried out using the Certainty Factor method. The purpose of this research is to create a website-based application with an expert system that can be an alternative to find out the type of facial skin in order to determine the right skincare product, as a substitute for consulting a doctor. The results of the study stated that manual calculations using the Certainty Factor method had the same final results as calculations in the application.